Living, Caring, Learning - Thinking outside the box to solve care challenges in a rare blood disorder - Hibner Sandra (The Journal of Haemophilia Practice)
A specialist nurse for over 20 years, Sandra reflects on her experience of finding ways to deliver effective care for a young girl with a very rare clotting disorder. Symptoms of the girl’s disorder were evident from birth and through an emergency use request Sandra and the care team enabled her family to access a treatment that at the time was in clinical trial. Poor venous access meant there was a need to adapt how treatment was administered and she worked with the girl’s parents to ensure that she was treated effectively. Alongside educating the parents, Sandra highlights the importance of her role in educating co-workers and other hospital staff likely to come into contact with the girl, to ensure that she always had access to timely and appropriate care. She also reflects on other instances where thinking creatively enabled patients in her care access to treatments that may not otherwise have been accessible. Now retired, Sandra continues to be involved in advocacy for people with bleeding disorders.